ショウワ キチ デノ スイジュン ソクリョウ ト ジュウリョク ソクリョウ - 神沼, 克伊; カミヌマ, カツタダ; 阿部, 馨; アベ, カオル; 田中, 等; タナカ, ヒトシ; Kaminuma, Katsutada; Abe, Kaoru; Tanaka, Hitoshi (1984)
P(論文) 1979年と1982年, 第20次および第23次日本南極地域観測隊により, 南極昭和基地に水準測量網が完成された。観測は国土地理院の一等水準測量作業規程により実施され, その精度内での結果を得た。また, 1979年には西オングル島の測地基準点を中心に25点での重力測量が実施された。1982年には, ラングホブデ沖の小島の測地基準点5点と昭和基地の水管傾斜計脇に取り付けられた水準点で重力測量を実施した。 Leveling routes for detecting the ground tilt caused probably by the regional deglaciation were established by the 20th and 23rd Japanese Antarctic Research Expedition (JARE-20 and -23) in East Ongul Island, Antarctica. The leveling surveys were carried out according to the first order leveling survey method of Geographical Survey Institute in Japan during the winter seasons of 1979 and 1982. The accuracy of the surveys between the leveling points was better than ±0.4mm. Gravity surveys using LaCoste-Romberg gravimeter model G were also carried out in 1979 and 1982. Twenty-five gravity stations were established in West Ongul Island in 1979. The gravity at six stations out of twenty-five was also measured by JARE-19 and -22 in 1978 and/or 1981. The gravity values of the two or three independent surveys at the same station were consistent with each other within the accuracy of 0.1 mgal. Five gravity stations were also established at the geodetic control points in small islands off Langhovde, and three stations near the water tube tiltmeter of two components at Syowa Station. departmental bulletin paper